Transport Strategy to Improve Accessibility in Developing Countries - Roberts, Peter (World Bank, Washington, DC, 2014)
In developing countries disabled people and the elderly are more likely to be among the poor. Moreover, exclusion increases the costs associated with disability to constrain disabled people from breaking out of poverty. Improved access and mobility are important factors in reducing poverty and can facilitate the participation of people with disabilities in economic, social, and political processes. Many countries have legislation requiring that these challenges be addressed but effective responses are generally very limited. Action to improve the situation is constrained by the serious shortage of data on the access and mobility needs of disabled and elderly people as well as by resource constraints. This paper outlines guidance for addressing the access and mobility needs of disabled and elderly people in the context of the World Bank's mission to reduce poverty and discusses the main challenges for providing inclusive transport. It draws attention to opportunities to learn from transport interventions and to current research. The paper describes the main activities being fostered by the transport sector in the World Bank. These aim to raise awareness of proven good practice in setting policies and strategies.